HEGEMONY OF MODERNITY AND MASDUN’S MIMICRY PROCESS IN PASAR HEWAN BY N. H. DINI (BHABHA’S POSTCOLONIAL DISCOURSE) - Neisya - - (HOLISTICS, 2018)
People who live in the third world country are usually easy to be persuaded with the word of modernity. They like wanting to pursue a world of mirage that promises to live in the present and abound in luxury, but sometimes they are unable to withstand the lifestyle changes that immediately occur in their lives. This study tries to examine the phenomenon above, such as the story raised by N.H. Dini in one of her short stories entitled Pasar Hewan through descriptive method by using Bhabha's postcolonial perspective as the analysis framework. Through this study, the reader will be presented with a story that will invite us to reflect on how a modernization of lifestyle sometimes traps us in a vortex of pain that has no end and is not known how to return, as experienced by Masdun and the village community where he stay. Masdun, who at first was too passionate to change his life, eventually became skeptical and could not do much to the social changes that occurred massively in his surrounding community.